Good enough processing: what have we learned in the 20 years since Ferreira et al. (2002)? - Frances, Candice (Frontiers in Psychology, 2024)
Traditionally, language processing has been thought of in terms of complete processing of the input. In contrast to this, Ferreira, Bailey, and Ferraro (2002) put forth the idea of good enough processing. The proposal was that during everyday processing, ambiguities remain unresolved, we rely on heuristics instead of full analyses, and we carry out deep processing only if we need to for the task at hand. This idea has gathered substantial traction since its conception. In the current work, I review the papers that have tested the three key claims of good enough processing: ambiguities remain unresolved and underspecified, we use heuristics to parse sentences, and deep processing is only carried out if required by the task. I find mixed evidence for these claims and conclude with an appeal to further refinement of the claims and predictions of the theory.